Perancangan Aplikasi Sistem Basis Data Penelitian dan PPM (Balit) Pada Jurusan Teknik Elektro Politeknik Negeri Pontianak - Budianingsih -; Pausta Yugianus (Informatika Universitas Siliwangi, 2020)
The purpose of this research is to build a database of research and community service. Which so far to monitor or see the title of research and community service is to look at the SK (Decree) research and PPM PNBP that has been published, or see a collection of research and community service lists stored on Microsoft Excel software. This certainly makes it very difficult for parties with an interest in research data and ppm. Where these data are used for accreditation and promotion. Related parties must come to the department administrator to request data stored on the department's computer. The design of this application uses the UML (Unified Modeling Language) modeling language. This application development methodology is based on Design research Science for Information System. For making this application using CodeIgniter and with a MySQL database. With the application of the research database and ppm, it is hoped that it will facilitate the parties concerned in managing data and data search